The Modern Game of Doubles: A Tactical Perspective - Black, Wayne; Van de Braam, Merlin (ITF Coaching & Sport Science Review, 2012)
This article focuses on the game of doubles from a tactical perspective. The primary author, a four-time doubles Grand Slam Champion, outlines some observations of how the game of modern doubles has evolved, whilst still retaining some of the core aspects that the game is unique for. The article then focuses specifically on the long-term development of the doubles player, and emphasises not only tactics, but the physical and mental requirements that are demanded of a player on route to the highest levels of the game.